KETERKAITAN JALUR TRANSPORTASI DAN INTERAKSI EKONOMI KABUPATEN KONAWE UTARA DENGAN KABUPATEN/KOTA SEKITARNYA - Silondae, Sutami (JPEP (Jurnal Progres Ekonomi Pembangunan), 2016)
This study aimed to find out and empirically analyze: 1) the economic interaction between North Konawe regency and its surrounding cities/regencies, 2) the impact of transportation on the economy of North Konawe regency. The study used a descriptive research design. Types of data used were quantitative and qualitative data. Sources of data were primary and secondary data. Techniques of data analysis used were observation, interview, and documentation. Data analysis used an analysis of the condition of transportation route, gravitation of economic interaction, index of economic interaction, quadrant, and used a deskriptive analysis. Result of the study concludes that: 1) the condition of transportation route which connects North Konawe regency and its surrounding cities/regencies in 2013 shows that the most severely damaged road is in Morowaliregency, which spans 122.438,47 km2 or 57.89%, followed by the road in Konawe regency which spans 814.39 km2 or 81%, and the road in Kendari city which spans 268.92 km2or 52%. The economic interaction between North Konawe regency its surrounding cities/regencies shows that the biggest interaction is with Kendari city, followed by Konawe regency, and then Morowali regency. People who are mobilizing themselves prefer Kendari city due to factors of the needs for goods and service such as healthcare service.Â  Kendari city had a superior interaction with North Konawe regency, whereas Morowali regency was in the position of developing interaction, and Konawe regency was categorized into a region with potential interaction. 2) the impact of transportation on the economy of North Konawe regency was positive, as well as on the Gross Regional Domestic Product (GRDP), which amounted to Rp. 3.074,68 or 0.53 percent. Â  Keywords: Transportation Route, Economic Index